OncomiRs as noncoding RNAs having functions in cancer: Their role in immune suppression and clinical implications - Otmani, Khalid; Rouas, Redouane; Lewalle, Philippe (Frontiers in Immunology, 2022)
MicroRNAs (miRNAs) are non-coding RNA known as critical posttranscriptional regulators of messenger RNA (mRNA) translation into proteins. By regulating gene expression, miRNAs enhance or inhibit cancer development and participate in several cancer biological processes, including proliferation, invasion and metastasis, angiogenesis, chemoresistance, and immune escape. Consistent with their widespread effects, miRNAs have been categorized as oncogenes (oncomiRs) or tumor suppressor miRNAs based on their inhibition of a variety of tumor-suppressive or oncogenic mRNAs, respectively. Endogenous miRNAs regulate not only different cellular pathways in tumor cells but also in immune cells in the tumor microenvironment. MiRNAs have emerged as important mediators of intercellular communication between immune and tumor cells. MiRNAs can be transferred from cancer cells to recipient cells where they regulate targeted gene expression through extracellular vesicles (EVs). Extravesicular miRNAs were proven to be key components of the tumor microenvironment by orchestrating communication between cancer cells and the surrounding stromal cells to promote cancer progression and drive immune suppression. This review outlines recent advances in understanding the role of oncomiRs in enhancing cancer and how they promote its aggressive characteristics. It aims to intensely discuss the role of oncomiRs in modulating the cancer-related immune response in the tumor immune microenvironment. Additionally, it should be considered that understanding of the mechanism of oncomiR-related immune suppression will facilitate the use of miRNAs as biomarkers of impaired antitumor immune function and make them ideal immunotherapeutic targets.